Calculation of the spin-lattice coefficients of Gd3+ in caF2 using a point-charge model for the crystalline fieId. - Calvo, R.; Passeggi, M.C.G.; Tovar, M. (American Chemical Society's, 1971)
Fil: Calvo, R. Comisión Nacional de Energía Atómica; Argentina